THE EFFECT OF SOCIAL CAPITAL ON WELFARE IN INDONESIA - Jumirah Jumirah; Heni Wahyuni (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
Studies into the impact of social capital on welfare are currently growing. However, studies for the case of the developing countries, including Indonesia, are still very rare. Therefore, this paper aims to analyze the impact of social capital on welfare in Indonesia. In this study, social capital is measured by three indicators, namely, trust, cooperativeness and the social network (a person’s participation in community activities).Welfare is measured by household expenditure for food and non-food items. The data are acquired from the Indonesian Family Life Surveys for the years 2007 (IFLS4) and 2014 (IFLS5). This research uses instrumental variables to address the endogeneity issue on social networking (participation in community activities), which is a potential two-way causal relationship. It means that individuals with higher welfare (income) have a higher possibility of participating in community activities, since their participation in community activities is a leisure activity and the utilization of leisure is higher for higher-income people.Using the Instrumental Variables (IV) method and marital status as an instrument, the study found that social capital has a significant impact on welfare. An increased participation in community activities will improve ones welfare by 11.7 percent. Moreover, an increase of cooperativeness by one percent, would increase the welfare by 0.2 percent. On the other hand, trust has a negative relationship with welfare. It means that an increase in trust among individuals by one percent will cause household expenditure on food and non-food items to drop by 0.3 percent.It may imply that higher trust will cause lower transaction costs, which will reduce the expense of individuals buying food and non-food items. Since the coefficient of IV is larger than the coefficient in the OLS estimation, it indicates the absence of reversed causality. The results of this study have an implication for policy decision making which suggests that the policy decision makers should consider the impact of social capital on welfare and support the increase of individuals’ participating in community activities.